1986
DOI: 10.1117/12.938884
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Interactions During Laser Cutting

Abstract: Most laser cutting systems utilise a gas jet to remove molten or vaporised material from the kerf.The speed, economy and quality of the cut can be strongly dependent on the aerodynamic conditions created by the nozzle, workpiece proximity and kerf shape. Adverse conditions can be established that may lead to an unwelcome lack of reproducibility of cut quality.Relatively low gas nozzle pressures can result in supersonic flow in the jet with its associated shock fronts.When the nozzle is placed at conventional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…As Fieret et al showed 7,8 that the surface pressure depends on the distance between the exit nozzle and the target surface. Striosopy images can evidence so.…”
Section: B Strioscopy Of the Gas Jet With Targetmentioning
confidence: 99%
See 3 more Smart Citations
“…As Fieret et al showed 7,8 that the surface pressure depends on the distance between the exit nozzle and the target surface. Striosopy images can evidence so.…”
Section: B Strioscopy Of the Gas Jet With Targetmentioning
confidence: 99%
“…Figure 6 presents the total pressure on target surface ͑and so, on the front of hole during drilling͒ as function of WD. As shown by Fieret,7,8 curves correspond to typical profiles of a jet without MSD. Pressure decreases for WD coming from 0 to 3.5 mm.…”
Section: B Strioscopy Of the Gas Jet With Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the thicker the workpiece is, the lower the capability of the assist gas jet has in removing molten material from the cutting front. Insufficient gas flow through the cutting front decreases the cutting speed, and generates burr, dross and recast layers (3)- (5) . In order to improve the cutting speed and the capability to remove molten material, and, furthermore, to save gas consumption, real-time positioning control of the relative displacement between the lens and the assist gas jet nozzle in laser beam cutting machines (off-axis control) has been proposed, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%